Essentials of the California Verbal Learning Test : CVLT-C, CVLT-2, & CVLT3 - Farrer, Thomas J. (Thomas Jeffrey), 1983-; Drozdick, Lisa Whipple (Essentials of psychological assessment series., 2020)
"During development in childhood, verbal learning and memory are key to success in school and language acquisition and development. A large portion of time is spent in activities requiring retention of verbal information, such as conversations with parents and peers, reading, and interacting with digital devices. The ability to encode and retain verbal information remains elemental throughout the lifespan as much learning and social interaction requires adequate verbal learning and memory ability"--